Effects of different types of oil and storage conditions on acrylamide formation in sweet potato Ipomoea batatas L. lam chips - Lim, Pek Kui (2014)
Acrylamide, a carcinogen compound is usually generated in carbohydraterich processed food during heat treatment. The objectives of this study were firstly to evaluate the precursors of acrylamide formation in sweet potato chips via ten similar consecutive deep-frying experiments with each type of vegetable oil (palm olein, coconut, canola and soya bean) at the temperature of 180 °C for 2 minutes. The second objective was to determine the effect of storage (at 15 °C and 28 °C) of sweet potato roots on acrylamide prescursors, i.e. sugars and free amino acids and correlations of precursors with the acrylamide formation. At each interval of the storage period (at 0, 14,21, 28, 35 and 42 days in 15 °C; whilst at 0, 5, 10, 15 and 25 days in 28 °C,respectively), sweet potato roots were sliced and deep fried into chips at the temperature of 180 °C for 105 seconds. Sweet potato samples for both first and second objectives were analysed for sugars and free amino acids analysis. The third objective of this study was to assess the influence of the lipids and lipids oxidation by the sweet potato powder model system at 180 °C on acrylamide formation. The role of lipids, reducing sugar and artificial antioxidant (i.e. butylated hydroxytoluene, BHT) in acrylamide formation were also studied. The last objective was to investigate the effects of adding free amino acids (asparagine, glutamine, glutamic acid, aspartic acid, alanine, serine and glycine) on the formation and reduction of acrylamide using sweet potato powder model. For the third and forth objectives, the reactants of the binary and ternary model (asparagineglucose/ fructose/sucrose, asparagine-palm olein/soya bean oil and asparagine-glucose-palm olein/soya bean oil for the third objective; whilst amino acid-glucose and amino acid-asparagine-glucose for the last objective, respectively) were singly homogenized in silica gel 60 by using a ceramic pestle. Additionally, oils sample (palm olein, soya bean oil, soya bean oil with added BHT, coconut oil and canola oil) and free amino acids (asparagine, glutamine, glutamic acid, aspartic acid, alanine, serine and glycine) were singly homogenized in sweet potato powder model system. All models were heated under nitrogen at 180 °C in closed test tube for 20 min in a laboratory oven. The general linear model (GLM) analysis of variance (ANOVA) was applied to the first objective analysis, whilst the ANOVA and Tukey’s multiple comparisons test was also used to assess the significant of differences for the entire study of comparison test. However, Pearson correlation was used in the second objective to assess the relationships of the reducing sugars and acrylamide concentration. Furthermore, multivariate analysis was applied by performing orthogonal partial least squares (OPLS) regression analysis to determine the correlations between the metabolites (glucose,fructose, sucrose, reducing sugars, total sugars, and free amino acids) and acrylamide formation. The analysis of sugar and reducing sugars was performed by a high performance liquid chromatography (HPLC) equipped with a refractive index (RI) detector. Free amino acids concentrations were determined with an EZ:faast amino acid analysis kit and were analysed by a gas chromatograph (GC) that was equipped with a flame ionization detector (FID). Sweet potato chips were homogenized by a processor and samples were cleaned by Oasis HLB and MCX cartridges before acrylamide analysis was carried out. The acrylamide concentrations were determined by liquid chromatography equipped with a triple-quadrupole mass spectrometer(LC/MS-MS). In addition, an atmospheric pressure chemical ionization (APCI) source was used. During the deep-frying experiments of sweet potato chips, acrylamide was detected in the range of 296 to 2849 μg/kg. Raw sweet potato roots were also found to contain acrylamide precursors (glucose & fructose, free asparagine). Meanwhile, multivariate data analysis revealed that the sugars (glucose, fructose, sucrose), total reducing sugars, total sugars, and free amino acids (asparagine, serine, alanine, threonine) were positively correlated to acrylamide formation, whilst glycine and valine were negatively correlated to acrylamide formation. Furthermore, the model study confirmed that free amino acids (asparagine, glutamine, glutamic acid, aspartic acid, alanine, serine, glycine) are the precursors of acrylamide formation, and asparagine was the predominant amino acid. The storage experiment showed positive correlation between the concentration of acrylamide and with those of serine and alanine; however, no significant different was found between the treated and the controlled samples with the addition of serine and alanine. The results were probably caused by the synergism by serine and alanine with other chemical compositions in sweet potato roots during storage. On the other hand, there was insignificant acrylamide reduction by gylcine; this was perhaps attributed to the abundant of sugars in the samples; as a result, there was no competition between glycine and asparagine for the available carbonyl compound (in sugars). Therefore, glycine might not be a suitable additive for reducing acrylamide formation in sweet potato products. Although, lower acrylamide concentration in sweet potato chips was mostly detected by using a frying oil with medium degree of unsaturation (e.g palm olein), no specific oil type was found to be superior; this may be due to oil deterioration after many repeated use of all oil tested in the study for frying. Moreover, the study also indicated that combination of total unsaturated fatty acid and total oxidation of oil influenced the acrylamide formation positively (r2 = 0.986, p = 0.000). The study concluded that the lipids should not be ignored in the generation of acrylamide.